Risk and outcomes of aortic valve endocarditis among patients with bicuspid and tricuspid aortic valves. Issue 1 (16th May 2017) - Kiyota, Yuka; Della Corte, Alessandro; Montiero Vieira, Vanessa; Habchi, Karam; Huang, Chuan-Chin; Della Ratta, Ester E; Sundt, Thoralf M; Shekar, Prem; Muehlschlegel, Jochen D; Body, Simon C
Abstract : Objective: Patients with structural abnormalities of cardiac valves, including bicuspid aortic valve (BAV), are said to be at higher risk of infective endocarditis (IE). We sought to determine the risk of IE of the BAV compared with the tricuspid aortic valve (TAV) and to determine the risk of aortic valve replacement and mortality after IE. Methods: From medical records of two US and one Italian hospitals, patients with their first episode of IE of any native valve were identified. In the US cohort 42 patients with BAV and 393 patients with TAV with IE occurring between 1 January 2000 and 30 June 2014 were identified. In the Italian cohort 48 patients with BAV and 341 patients with TAV with IE underwent valve replacement surgery between 1 January 2000 and1 November 2015. The risk of IE for BAV and TAV and subsequent outcomes were determined after matching to patients without IE. Results: After adjustment for risk factors, the risk of IE in the US cohort was 23.1 (95% CI 8.1 to 100, p <0.0001) times greater for BAV than TAV. Patients with BAV with IE were more likely to have an aortic root abscess. Within the subsequent 5 years, BAV patients with IE were more likely to undergo valve replacement (85%) than TAV patients with IE (46%). Patients with IE were at increased risk of death. The findings were similar in the Italian cohort. Conclusions: Patients with BAV are at markedly increased risk of IE and aortic root abscess than patients with TAV. Increased risk of IE in patients with BAV indicates they may be a candidate group for long-term trials of antibiotic prophylaxis of IE.